2013
DOI: 10.1111/twec.12125
|View full text |Cite
|
Sign up to set email alerts
|

The Trade Effects of US Anti‐dumping Actions against China Post‐WTO Entry

Abstract: Since China's entry into the WTO, US anti‐dumping (AD) actions against China have increased, particularly with respect to multiple petitions. Distinguishing between US single and multiple petitions, we examine the trade effects of US AD actions against China based on an unbalanced panel of quarterly trade data. The results show that a US single petition investigation greatly restrains US imports of the filed products from China but also causes more significant import diversion from non‐named countries. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…Thus, our paper is much closer to the original questions explored by Prusa (1997Prusa ( , 2001. A recent paper that is closest to ours is that of Shen and Fu (2014). Using quarterly data on US imports, they too explore the impact of US antidumping duties on China and find that US antidumping duties against China restrict US imports from China but increase US imports from other countries in the long run.…”
supporting
confidence: 53%
“…Thus, our paper is much closer to the original questions explored by Prusa (1997Prusa ( , 2001. A recent paper that is closest to ours is that of Shen and Fu (2014). Using quarterly data on US imports, they too explore the impact of US antidumping duties on China and find that US antidumping duties against China restrict US imports from China but increase US imports from other countries in the long run.…”
supporting
confidence: 53%
“…More recent empirical studies have found that protectionist measures implemented since the start of the global financial crisis are affecting global trade flows negatively (Henn and McDonald ). Specific to nontariff trade barriers, empirical studies also found that the antidumping measures against China deterred Chinese exports (Shen and Fu ; Vandenbussche and Viegelahn ). Following these findings, we propose our fourth hypothesis: HYPOTHESIS 4 Export performance of China (India) of one product is negatively associated to (a) tariff increases and (b) antidumping measures related to this product .…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Brenton (2001), Prusa (2001) and Park (2009), among others, have documented the trade destruction effect empirically. Specifically, Shen and Fu (2014) find that the US import tariffs against China have led to significant reductions in exports of products covered under the applicable tariff lines from China to the US. The findings of Chandra (2017) show that, on average, a 35% reduction has been observed in China's exports of products covered under the levied tariff lines to the tariff levying countries.…”
Section: Introductionmentioning
confidence: 99%